Justice And Welfare - EN37 - 202101 - Berckholtz Benavides, Klaus (2021)
Normative economics and political philosophy are both concerned with the evaluation of social states and distributions: what constitutes a better economic distribution, or a fair way to sustain social and economic cooperation? How do the values of freedom, justice and welfare relate? The course centers around two broad families of approaches: those that focus on fairness or justice, and those that evaluate on the basis of welfare improvements. Topics to be considered include utility theory, economic efficiency, distributive justice and the morality of capitalism and socialism.